RANCANG BANGUN SISTEM INFORMASI OBYEK WISATA BERBASIS WEB MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Oni Yuliani; Joko Prasojo (Institut Teknologi Dirgantara Adisutjipto, 2015)
The development of today's technology has been developing very rapidly and carry a very big change because with the technology information can be obtained quickly, accurately and not limited by time and place. One o f the growing sectors in technology development is in the field of tourism which contributes to distribute information about the attractions more interactive, especially through Internet technology. Yogyakarta has a variety of tourist attractions that are so beautiful, but not many people know the various tourist attractions in the area. Information on tourist places will be known if given a forum to exchange information on the matter in the form of a website. In order to generate tourism website in accordance with the wishes of users, the necessary methods of User Centered Design (UCD) based to the user. It is intended to provide information for tourists so it will be easier to plan excursions according to what they want without hesitation choose the desired attraction. Tourism information system was built using PHP as a programming language and MySQL as a database manager. This information system design using the UCD that engage users by providing input in the form of a questionnaire. This information system contains the profiles sights, means of transportation used and distance traveled. Other facilities that can be enjoyed for information about travel agents who can serve a trip out of town, and the inn (hotel). To implement this system needs the previous test program testing and system testing and then be evaluated. The information system created is a system that is capable of displaying objects on the map and provide information on the map if the object is selected, the user can view more detailed position of an object to be searched. For site owners can perform additional object data without having to perform the construction site from scratch, in this case both the data on a map or information. By making this system the objects displayed on the map always updates that facilitate and assist the user in doing excursions in Yogyakarta.